Osteoimmunology drives dental implant osseointegration: A new paradigm for implant dentistry - Luis Amengual-Peñafiel; Luis A. Córdova; M. Constanza Jara-Sepúlveda; Manuel Brañes-Aroca; Francisco Marchesani-Carrasco; Ricardo Cartes-Velásquez (Elsevier, 2021)
There is a complex interaction between titanium dental implants, bone, and the immune system. Among them, specific immune cells, macrophages play a crucial role in the osseointegration dynamics. Infiltrating macrophages and resident macrophages (osteomacs) contribute to achieving an early pro-regenerative peri-implant environment. Also, multinucleated giant cells (MNGCs) in the bone-implant interface and their polarization ability, maintain a peri-implant immunological balance to preserve osseointegration integrity. However, dental implants can display cumulative levels of antigens (ions, nano and microparticles and bacterial antigens) at the implant-tissue interface activating an immune-inflammatory response. If the inflammation is not resolved or reactivated due to the stress signals and the immunogenicity of elements present, this could lead implants to aseptic loosening, infections, and subsequent bone loss. Therefore, to maintain osseointegration and prevent bone loss of implants, a better understanding of the osteoimmunology of the peri-implant environment would lead to the development of new therapeutic approaches. In this line, depicting osteoimmunological mechanisms, we discuss immunomodulatory strategies to improve and preserve a long-term functional integration between dental implants and the human body.Scientific field of dental science: implant dentistry.